The importance of periprostatic fat tissue thickness measured by preoperative multiparametric magnetic resonance imaging in upstage prediction after robot-assisted radical prostatectomy - Emre Uzun; Muhammed Emin Polat; Kazim Ceviz; Erkan Olcucuoglu; Sedat Tastemur; Yusuf Kasap; Samet Senel; Ozkan Ozdemir (Investigative and Clinical Urology, 2024)
Purpose: We analyzed the surgical results of patients who were treated and followed up for prostate cancer in our clinic to predict the relationship between periprostatic adipose tissue and patients with and without pathologically upstaged disease. Materials and Methods: The study included patients who had undergone robot-assisted radical prostatectomy and preoperative multiparametric prostate magnetic resonance imaging between 18 February 2019 and 1 April 2022. The patients were divided into two groups, and the surgical and transrectal ultrasound-guided biopsy pathology results were compared according to tumor grade and distribution in 124 patients who met the selection criteria. We analyzed the relationships between upgrading/upstaging and periprostatic adipose tissue thickness (PPATT) and subcutaneous adipose tissue thickness (SATT) as measured in magnetic resonance imaging. Results: The median PPATT was 4.03 mm, whereas the median SATT was 36.4 mm. Upgrading was detected in 45 patients (36.3%), and upstaging was detected in 42 patients (33.9%). A receiver operating characteristic regression analysis revealed that a PPATT >3 mm was a predictive factor for upstaging after radical prostatectomy (area under curve=0.623, 95% confidence interval [CI] 0.519–0.727, p=0.025). Multivariate logistic regression analyses revealed that prostate specific antigen density ≥0.15 ng/mL/cm3 (odds ratio [OR] 5.054, 95% CI 2.008–12.724, p=0.001), International Society of Urological Pathology grade ≥4 (OR 9.369, 95% CI 2.109–21.626, p=0.003) and higher PPATT (OR 1.358, 95% CI 1.081–1.707, p=0.009) were independent risk factors for upstaging after radical prostatectomy. Conclusions: We believe that the PPATT may be a predictive indicator for upstaging after robot-assisted laparoscopic radical prostatectomy.